Design and Implementation of IoT-Based Water Pipe Pressure Monitoring Instrument - Hollanda Arief Kusuma; Rady Purbakawaca; Irwan Rudy Pamungkas; Luthfy Nizarul Fikry; Sonny Seftian Maulizar (Jurnal Elektronika dan Telekomunikasi, 2021)
The water pressure monitoring system in the PDAM pipeline networks has been successfully developed for operation and maintenance of water leaks in a real-time manner. This research aims to design a water pressure monitoring system in operational piping networks to identify anomalies as early as possible. The system is built using a microcontroller, a 1.2 MPa fluid pressure sensor and a control system equipped with a GSM wireless communication module, an Analog to Digital Converter module with 16-bit resolution, a real-time clock peripheral, an OLED display 128x64, and a micro SD card. The developed system was tested in a pressure range of 0.200 - 0.800 bar with 30 repetitions with a RMSE of 0.058 bar. This system has a deterministic coefficient of 0.885 against a standard manometer. The system implemented in the field successfully sends data to the server with a success rate of 96.0%. Data is displayed on a monitoring dashboard that can be accessed via a computer or smartphone.